Cycles in Hydrologic Intensification and De‐Intensification Create Instabilities in Spring Nitrate‐N Export C‐Q Relationships in Northern Temperate Forests - I. F. Creed; D. A. Aldred; J. A. Leach; K. L. Webster; M. Bieroza (Water Resources Research)
Abstract Northern temperate forests are experiencing changes from climate and acidification recovery that influence catchment nitrate‐nitrogen (N) flushing behavior. N flushing behavior is characterized by metrics such as: (a) N flushing time—the exponential decrease in stream N concentration during the peak snowmelt episode; and (b) N concentration (C) and discharge (Q) hysteresis metrics—flushing index (FI) and hysteresis index (HI)—representing the slope, direction, and amplitude of the C‐Q loop. We hypothesized that climate‐driven hydrologic intensification results in longer N flushing times, lower FI (less flushing to more diluting), and lower HI (less proximal to more distal N sources). We tested this hypothesis using four decades of data from two headwater catchments. Hydrologic intensification was estimated by changes in the ratio of potential evapotranspiration to precipitation and the ratio of actual evapotranspiration to precipitation. From 1982 to 2005, a period characterized by hydrologic intensification and a decline in atmospheric acidic deposition, we observed a decrease in C and Q. This led to stable C‐Q patterns that reflected the flushing (positive FI) of proximal N sources (positive HI). However, from 2006 to 2019, a period of hydrologic de‐intensification coupled with an ongoing decline in atmospheric acidic deposition was associated with a continued decrease in C but an increase in Q, leading to unstable C‐Q patterns that reflected a shift from proximal (positive HI) toward distal N sources (negative HI). C‐Q instability was less variable in the catchment with a large wetland, indicating the potential of wetlands to buffer against changing climate conditions.